2022
DOI: 10.3389/fpsyg.2022.753774
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family Socioeconomic Status on Primary School Students’ Emotional Intelligence: The Mediating Effect of Parenting Styles and Regional Differences

Abstract: Select 180 primary school students from a city primary school in Shanghai, a developed area in eastern China, and 146 primary school students from a rural primary school in Jingzhou, a centrally underdeveloped area, as subjects. The method of scale is used to explore the influence of family socioeconomic status on the emotional intelligence of primary school students, and the mediating role of parenting styles in this influence and the difference in this effect in the two regions. The results show that: (1) Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The test-retest reliability ranged from 0.67 to 0.89, with an average of 0.776 [31]. Since, Yue did a lot of research in China based on the EMBU scale and adapted the EMBU scale to the actual situation in China, many Chinese scholars have also adopted their modified scales, and all of these studies have confirmed that their scales have good reliability and validity [32]. Though favoritism has been identified to be culture-specific, cross-cultural stability of the EMBU based on data from Chinese subjects is satisfactory [33,34].…”
Section: Perceived Parenting Stylesmentioning
confidence: 99%
“…The test-retest reliability ranged from 0.67 to 0.89, with an average of 0.776 [31]. Since, Yue did a lot of research in China based on the EMBU scale and adapted the EMBU scale to the actual situation in China, many Chinese scholars have also adopted their modified scales, and all of these studies have confirmed that their scales have good reliability and validity [32]. Though favoritism has been identified to be culture-specific, cross-cultural stability of the EMBU based on data from Chinese subjects is satisfactory [33,34].…”
Section: Perceived Parenting Stylesmentioning
confidence: 99%